2020
DOI: 10.1259/dmfr.20190348
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a deep learning system for diagnosing Sjögren’s syndrome using ultrasonography images

Abstract: Objectives: We evaluated the diagnostic performance of a deep learning system for the detection of Sjögren’s syndrome (SjS) in ultrasonography (US) images, and compared it with the performance of inexperienced radiologists. Methods: 100 patients with a confirmed diagnosis of SjS according to both the Japanese criteria and American-European Consensus Group criteria and 100 non-SjS patients that had a dry mouth and suspected SjS but were definitively diagnosed as non-SjS were enrolled in this study. All the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…When assessing glandular disorders, radiologists demonstrated better agreement ( k = 0.65) for disorders of visibly larger glands (parotid) as opposed to smaller glands ( k = 0.51) obstructed by bony anatomy (submandibular gland) [ 13 ]. This deemed machine learning more sensitive to glandular anomalies but was also equally prone to making mistakes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When assessing glandular disorders, radiologists demonstrated better agreement ( k = 0.65) for disorders of visibly larger glands (parotid) as opposed to smaller glands ( k = 0.51) obstructed by bony anatomy (submandibular gland) [ 13 ]. This deemed machine learning more sensitive to glandular anomalies but was also equally prone to making mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…This deemed machine learning more sensitive to glandular anomalies but was also equally prone to making mistakes. Kise developed deep-learned systems to diagnose Sjogren's syndrome from both ultrasound imaging ( parotid gland : Ac = 0.89, Sn = 0.90, SP = 0.89; submandibular gland : Ac = 0.84, Sn = 0.81, Sp = 0.87) [ 13 ] and computed tomography (Ac = 0.96, Sn = 1.00, SP = 0.92) [ 12 ]. The authors found that only clinicians with >30 years of experience were able to compete (Ac = 0.98, Sn = 0.99, Sp = 0.97) with the deep learning algorithm (Ac = 0.96, Sn = 1.00, Sp = 0.92) in diagnosing salivary gland disorders from 3D CT images [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on the expression of inflammatory cytokines genes, ANN, SVM, and RF were all capable of distinguishing oral lichen planus from other white lesions of the oral mucosa (Jeon et al 2015). When used for recognizing steatosis (i.e., abnormal retention of lipids) of the salivary gland parenchyma in ultrasonography images, ANN was superior to inexperienced radiologists in differentiating patients with true Sjögren’s syndrome from those with xerostomia (Kise et al 2020).…”
Section: Applications Of Ai In Dentistrymentioning
confidence: 99%